2021
DOI: 10.1002/nop2.1018
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset PTSD and coping strategies for frontline nurses during the COVID‐19 epidemic in China

Abstract: Aim To evaluate the late‐onset post‐traumatic stress disorder (PTSD) situation, coping strategies and social supports for frontline clinical nurses 6 months after involvement in fighting against coronavirus disease 2019 (COVID–19) outbreak in China. Design A cross‐sectional design. Methods We recently randomly distributed a questionnaire online to Chinese nurses who had taken care of COVID‐19 patients since the end of January 2020. The questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Problem-focused coping and seeking social support were negatively associated with PTSD among these firefighters. As positive coping strategies, social and organizational support may protect against late-onset PTSD among healthcare workers [ 49 , 50 ]. Very few studies have explored alcohol use in healthcare workers during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Problem-focused coping and seeking social support were negatively associated with PTSD among these firefighters. As positive coping strategies, social and organizational support may protect against late-onset PTSD among healthcare workers [ 49 , 50 ]. Very few studies have explored alcohol use in healthcare workers during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…We revealed that nurses were able to tackle the pandemic issue from their positive enthusiasm in dealing with the challenging situation created. Nursing intervention is efficiently accomplished when nurses have a positive interest about their workplace (Dobrowolska et al, 2021 ; Jiang et al, 2021 ). Positive interest at work results in higher levels of service quality (Othman & Nasurdin, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that a nurse's negative attitude significantly affects providing appropriate nursing care (Rayner et al, 2019 ; Weare et al, 2019 ). However, developing coping strategies enhances the nurses' interest in handling critically ill patients (Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the multiple linear regression provide further evidence that self‐efficacy predicts the QWL. It is because the higher the self‐efficacy of nursing managers, the higher their commitment to work (Jiang et al, 2021), the greater their confidence in management, and the more courageous they are in coping with difficult situations. These traits often manifest in greater nursing management competence and pursuing higher‐value goals.…”
Section: Discussionmentioning
confidence: 99%